143 NOLU BEŞİKTAŞ ŞER'İYYE SİCİLİ (H. 1218-1220; M. 1803/1804-1805/1806) - KILIÇ, BAHAR (Fırat Üniveristesi, 2019)
Şer'iyye sicilleri hakkında değerlendirme yaparken; Şer'iyye Mahkemeleri, bu mahkemelerin işleyişi, kadılık müessesesinden bahsettik. Daha sonra Şer'iyye Sicilleri hakkında bilgi verdikten sonra 143 NOLU BEŞİKTAŞ ŞER'İYYE SİCİLİ (H. 1218-1220; M. 1803/1804-1805/1806) sicil üzerinde çalıştık. Sicilin aslı İstanbul Müftülük Arşivindedir.

When evaluating the Sharia registers; We talked about the Sharia Courts, the functioning of these courts and the establishment of the judiciary. Later, after giving information about the Sharia Registers, BESIKTAS 143. We have worked on the registry of (H. 1218-1220; M. 1803/1804-1805/1806). The original register is in the Istanbul Mufti's Archive.
Besiktas shield registry with number 143 (H. 1218-1220; M. 1803/1804-1805/1806)
Keywords: Tarih